ANALISIS KONTEN EDUKASI DESAIN FASHION TERHADAP KEPUTUSAN PEMBELIAN JASA PADA MEDIA SOSIAL TIKTOK - Celina Ridha Afandi; Agus Hery Supadmi Irianti; Hapsari Kusumawardani; Nurul Aini (Jurnal Manajemen dan Pemasaran, 2025)
The many benefits of the TikTok application make researchers interested in developing their TikTok account with the username 'Celinaridha' to increase sales by uploading fashion design education content. The purpose of the study was to analyze fashion design education content, find out the decision to purchase custom-made fashion design and manufacturing services, and find out the effect of fashion design education content analysis on the decision to purchase custom-made fashion design and manufacturing services on TikTok social media. This study uses a quantitative approach. The population is the followers of the Celinaridha account in Indonesia, which is 110,538 followers. Sampling using the Slovin formula with a 10% error limit so that 99.909 were rounded up to 100. The data analysis technique used simple linear regression. The results of the study prove that the average educational content indicator has the highest content quality, the average purchasing decision variable is the highest recommendation from others. The results of the hypothesis test show that there is an influence of fashion design education content on purchasing decisions, this is known from the t-count value which is greater than the t-table, so Ha is accepted. Linear regression test shows that fashion design education content has an influence of 28.2% on the decision to purchase custom-made fashion design and manufacturing services on TikTok social media. The conclusion of this study is that there is a positive and significant influence between fashion design education content and purchasing decisions, as evidenced by the results of the t-test which shows that the t-count (2.296) is greater than the t-table (1.984) and a significance value of 0.038 which is smaller than 0.05 so that it can be stated that fashion design education content has an influence on the decision to purchase custom-made fashion design and manufacturing services on TikTok social media.